2007
DOI: 10.1002/ange.200604601
|View full text |Cite
|
Sign up to set email alerts
|

Templatkontrollierte Synthese eines π‐konjugierten Porphyrin‐Nanorings

Abstract: Rundgemacht: Das Biegen eines molekularen Drahtes um ein achtzähniges Templat führt zur Entstehung eines hochsymmetrischen, gürtelförmigen π‐Systems (grün im Bild), das sich durch Zugabe eines großen Überschusses an Pyridin unter Bildung des entsprechenden cyclischen Octamers freisetzen lässt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(24 citation statements)
references
References 37 publications
1
21
0
2
Order By: Relevance
“…The synthesis of these compounds have been reported previously. [19,50] Spectroscopy: Absorption spectra were measured on a Cary 4B UV/Vis spectrophotometer. The spectra were recorded between 300 and 850 nm at 300 nm per min with 0.5 nm spectral bandwidth.…”
Section: Methodsmentioning
confidence: 99%
“…The synthesis of these compounds have been reported previously. [19,50] Spectroscopy: Absorption spectra were measured on a Cary 4B UV/Vis spectrophotometer. The spectra were recorded between 300 and 850 nm at 300 nm per min with 0.5 nm spectral bandwidth.…”
Section: Methodsmentioning
confidence: 99%
“…[7] Size-exclusion chromatography in the presence of 1,4-diazabicyclo- Previously, we reported that the template is displaced from our porphyrin[8] nanoring with pyridine. [5] However, pyridine does not displace the template from 1 a·3 and 1 b·3, even when the complexes are dissolved in neat pyridine ([pyridine] = 12.4 m). More strongly coordinating amines, such as quinuclidine do displace the template from these complexes, when used in large excess ([quinuclidine] > 0.4 m ; 250 000 equiv).…”
Section: Dedicated To Professor Jeremy Sanders On the Occasion Of Hismentioning
confidence: 99%
“…The similar EM values of T6 and T6* probably accounts for their remarkably similar abilities to direct the synthesis of c-P6. The lower effective molarity measured in c-P7·T7* is close to the value previously measured for an 8-porphyrin nanoring complex, c-P8·T8 (EM ¼4 m), [3] and probably reflects the increase in flexibility with increasing molecular size, as well as the flexible À(CH 2 ) 2 À links in T7*. The lower cooperativity in c-P7·T7* must contribute to the lower yield in the template-directed synthesis of c-P7.…”
mentioning
confidence: 58%
“…[1] The introduction of flexibility into a multivalent ligand generally reduces its affinity for a complementary receptor, but the energy cost of restricting conformational freedom can be surprisingly small. [2] Recently we have shown that rigid radial oligo-pyridine templates can be used to direct the synthesis of complementary zinc porphyrin nanorings, [3][4][5] and that the nanoring-template complexes can have huge stability constants (up to 10 36 m À1 ). [3,4,6] Herein we report an investigation of flexible chiral templates based on cyclodextrin cores.…”
mentioning
confidence: 99%